DEVELOPMENT OF AUGMENTED REALITY LEARNING MEDIA IN GEOGRAPHY LEARNING WATER CYCLE MATERIAL AT SMA NEGERI 4 BANDA ACEH - Muslihatin Ikhyari; Abdul Wahab Abdi; Mirza Desfandi; Daska Azis; Ahmad Nubli Gadeng; Rosmadi Fauzi (GeoEco, 2025)
This study aims to develop augmented reality learning media on geography learning of water cycle material at SMAN 4 Banda Aceh. This research uses a 4D (four-D) research design, including the stages of define, design, develop, and disseminate. The sampling technique used was simple random sampling. The subjects of this study were 2 media and material experts and 28 students of class X7 SMAN 4 Banda Aceh. The object of research is the feasibility of media and materials, student responses and understanding. Data collection instruments used media and material feasibility test sheets, student response questionnaires, and test sheets. Analysis of feasibility data and student responses using the percentage formula while analyzing data on student understanding of the material using the value-gain. Analysis of media feasibility test obtained 89% with very feasible criteria. The feasibility of the material obtained 98% with very feasible criteria. Student response to the media obtained 97.3% with very good criteria. Student understanding shows an increase after learning to use augmented reality learning media on water cycle material. Based on the results of media and material feasibility tests, responses and understanding of students, it can be concluded that augmented reality learning media in learning geography of water cycle material is very feasible to use as one of the learning media for students at SMAN 4 Banda Aceh.